2001
DOI: 10.1046/j.1365-2133.2001.04445.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient satisfaction with care among dermatological outpatients

Abstract: Improving the physician's interpersonal skills can increase patient satisfaction, which is likely to have a positive effect on treatment adherence and health outcomes. Dermatologists succeeded better in establishing a good relationship with clinically more severely affected patients than with patients who were clinically mildly affected despite their quality of life being impaired. Thus, the inclusion of a patient-rated quality of life can be a useful measure in dermatology, as it enables clinicians to perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
184
7
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(214 citation statements)
references
References 24 publications
14
184
7
9
Order By: Relevance
“…Therefore, this measure appears a good candidate for the evaluation of the empathic nature of the consultation process between therapists and patients. This is important as it has been suggested that this process may be an important mediator for health outcomes [21,49,50] and one that is poorly addressed in practice [9,51]. Using routine CARE data, collected in practice, can assist therapists in evaluating their practice, in communicating with their patients and improving the quality of care provided.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this measure appears a good candidate for the evaluation of the empathic nature of the consultation process between therapists and patients. This is important as it has been suggested that this process may be an important mediator for health outcomes [21,49,50] and one that is poorly addressed in practice [9,51]. Using routine CARE data, collected in practice, can assist therapists in evaluating their practice, in communicating with their patients and improving the quality of care provided.…”
Section: Discussionmentioning
confidence: 99%
“…17 Satisfied patients are more likely to comply with their treatment, which is in turn associated with better clinical outcomes. 18,19 As patient satisfaction is considered to be a health care outcome and predictor of treatment utilization and adherence to treatment, care and support; therefore this study is conducted to assess the level of satisfaction of PLHIV and factors associated with PLHIV satisfaction with the services at ART centre.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 More research is needed, however, to provide insight into the determinants of health care use and the effectiveness of current health care facilities in treating specifi c skin diseases. Diseases of sebaceous glands and sweat glands a 0 = male, 1 = female, compared through Pearson's χ 2 .…”
Section: Discussionmentioning
confidence: 99%